Prognostic scales in advanced heart failure - Szczurek, Wioletta; Szyguła-Jurkiewicz, Bożena; Siedlecki, Łukasz; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2018)
Heart transplantation (HT) is the treatment of choice for patients with advanced heart failure (HF) who remain symptomatic despite optimal medical therapy. Due to the shortage of organs for transplantation and constantly increasing number of patients placed on waiting lists, accurate risk stratification is a crucial element of management in this population. Prognostic scales allow one to evaluate the patient prognosis, estimate the potential benefits of therapy and identify those patients most likely to benefit from advanced methods of treatment. In this review, we describe prognostic scales in advanced HF, concentrating on commonly used tools – the Heart Failure Survival Score (HFSS) and Seattle Heart Failure Model (SHFM) – as well as on the new promising scales for evaluating waiting list mortality and post-transplant outcomes.